The Impact of the Covid-19 Pandemic on the Stock Market: Empirically (Analysis of Indonesia's Major Stock Index) - William Tjong; Michael Michael (Institute of Computer Science (IOCS), 2021)
This study aims to investigate the impact of the COVID-19 pandemic on major stock indexes in Indonesia. Researchers construct weekly data panels from stock index returns, new cases of the COVID-19 pandemic and new confirmed cases of the COVID-19 pandemic. Pooled OLS regression, conventional t-test and Mann Whitney test were used to estimate the results in this study. The results in this study show that new cases of the COVID-19 pandemic and new confirmed cases of the COVID-19 pandemic are significantly related to weekly stock index returns, then this study shows that there is a difference in weekly returns before the COVID-19 pandemic with weekly returns when occurrence of the COVID-19 pandemic.